Synthesis and characterization of different graphite/chitosan ink ratio composition towards flexible strain sensor performance - Maizal Hairi, Nur Iffah Irdina; Md Ralib, Aliza Aini; Ahmad, Farah; Mat Hattar, Maziati Akmal (2022)
Flexible and stretchable strain sensors are getting vast attention to be implied in various wearable devices application. However, most conventional strain sensor is having limitations in achieving both high stretchability and sensitivity. Selection of materials for conductive ﬁllers and binders are crucial in producing the stretchable ink for strain sensors. Biopolymer materials such as chitosan started to be implied in various application such as gas sensor and electro-chemical sensor. Chitosan has advantages to be a good binder as it exerts sig-niﬁcant physical properties. Conductive ﬁllers such as graphite powder are known to be having good electrical conductivity. Hence, this paper aims to investigate the effect of different graphite/chitosan ink ratio composition towards ﬂexible and stretchable strain sensor performance. Three different graphite/chitosan ink ratios of 1:2, 1:3, and 1:4 were synthesized. The surface morphology shows that the graphite/chitosan ink ratio 1:2 has the most com-pact structure resulting to good adaptability, conductivity, and ﬂexibility. The XRD and FTIR results illustrate that graphite are successfully synthesized with chitosan solution. Measurement result shows that the highest strain detection range is also attainable by graphite/chitosan ink ratio of 1:2 at 83.3% strain and gauge factor of 5.44. This concludes that graphite/chitosan ink ratio of 1:2 is the optimum ratio as highest stretchability and sensitivity are recorded. Therefore, it is important to have an adequate amount of chitosan solution to obtain good ink structure and great performance of strain sensor.